Databases in networked information systems : 8th International Workshop, DNIS 2013, Aizu-Wakamatsu, Japan, March 25-27, 2013. Proceedings - Kikuchi, Shinji; Bhalla, Subhash; Madaan, Aastha (Lecture notes in computer science, 2013)
This book constitutes the refereed proceedings of the 8th International Workshop on Databases in Networked Information Systems, DNIS 2013, held in Aizu-Wakamatsu, Japan in March 2013. The 22 revised full papers presented were carefully reviewed and selected for inclusion in the book. The workshop generally puts the main focus on data semantics and infrastructure for information management and interchange. The papers are organized in topical sections on cloud-based database systems; information and knowledge management; information extraction from data resources; bio-medical information management; and networked information systems: infrastructure.